EFFECTIVENESS OF VEDIC MATHEMATICS ON ACHIEVEMENT IN MULTIPLICATION AMONG VIII GRADE STUDENTS - Dr. Precious Sheron and Ms. Harsimranjit Kaur (International journal of economic perspectives, 2022)
The present study was aimed to study the effect of Vedic Mathematics on achievement in multiplication among VIII grade students. A sample of 100 students was drawn randomly from class VIII studying in two CBSE schools of Amritsar city. Pre-Post experimental design was used for this present study. Experimental group was taught with Vedic Mathematics and controlled group was taught with conventional method. The study revealed that the mean score of experimental group is greater than the controlled group, which proves that Vedic mathematics is more effective than conventional method. Also this technique does not effect on the achievement of boys and girls of experimental group. Technique of Vedic mathematics is very helpful in competitive exam where learner have to solve lengthy mathematical problems in short span of time.